Analysis of the Effects of Factors, Which Affect Language Acquisition, on Four Basic Language Skills - Mehmet Özdemir; Dilan Çiftçi Ertürk (Sakarya University Journal of Education)
Lesson planning has always been of great importance in education and training processes. However, the lack of appropriate educational materials and the variable target group require the teacher to take an active role in this planning. In language acquisition, it is of great importance to develop four basic language skills at the same rate. However, many factors affect language acquisition. The aim of this study is to examine the effects of the factors, which affect language acquisition, on four basic language skills. In the study, document analysis technique, which is the basic qualitative research design, was used. The study first discusses which factors affect language acquisition. These factors are age, gender, ability, motivation, cognitive style, personality and teaching strategies, respectively. Then, the effects of each factor on the four language skills of speaking, writing, reading and listening were evaluated in detail. In this context, the practices that should be considered especially for different student groups that are encountered during the course were evaluated. It was determined that the diversity of methods and materials was especially important in the education process. In addition, it was emphasized that it is important for teachers to know the factors affecting the four basic language skills.